(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Lesson planning is one of integral aspects of teaching English overseas. However, it is likewise one of the most time-consuming and tedious. Many plans even involve certainly what the instructor should say during a class, and the anticipated response from students. This article discusses the peculiarities of lesson planning on English language.